WHOLE-BUILDING LCA ACCORDING WITH LEED V.4 - Gomes, Vanessa; Saade, Marcella; Silva, Maristela; Pulgrossi, Lizzie (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The LEED v4 Building Life-cycle Impact Reduction credit requires improved life cycle impacts compared to a baseline building. The baseline and proposed buildings must be functionally equivalent, i.e.: have comparable orientation and location, size, function and service life (>60 years) to fully account for maintenance and replacement but the proposed building must show improved energy performance. The life cycle assessment (LCA) scope is a cradle-tograve assessment of the building's structure and enclosure, following EN 15804:2013 system boundaries definition to encompass product, construction, use (except for energy and water), and end-of-life stages. Life cycle impacts must be calculated for six categories. A minimum 10% reduction relatively to the baseline must be demonstrated for global warming potential and other two impact categories, whilst no environmental impact category may increase by more than 5%. If all six impact categories are reduced by 10%, an extra point is awarded as Innovation credit. Typical cut-off criteria found in published whole-building LCAs is 5% of total mass and energy. Though LEED V4 tries to find the right balance between simplification whilst yielding meaningful LCA results, it applies a much larger cut-off rule. This paper explores the implications of such approach, through a Brazilian case study.